Comic Strips to Facilitate Students Reading Comprehension on Narrative Text - Br Siregar, Ayu Sartika; Fauzana, Riri (Journal of English and Arabic Language Teaching, 2024)
This study was conducted based on students' problems in reading, such as students' low reading comprehension abilities, lack of vocabulary mastery which makes them difficult to  understand  texts,  and  also  difficulties  in  pronunciation. Therefore, this research aims to find out whether the use of comic strips improves students' reading comprehension  skills  in  narrative texts,  in  class  X  MA  Al-Ittihad  Tapung  Makmur students. This research uses quantitative research. This research was  carried  out  in February-June 2024  at  MA  Al-Ittihad  Tapung Makmur.  The population in this study were all class as many as 26 students. The design of this research is a pre-experimental method with one group pre-test and post-test design. To collect data, researchers used a  reading  test  to  determine  students'  reading abilities which consisted of multiple choice questions with 20 questions. The results of data analysis show that the average score of students after being taught using Comic strips (84.04) is higher than before being taught using Comic strips (53.85). It  can  be  concluded  that  there  is  an  influence between  students'  reading comprehension abilities before and after being taught using Comic strips in class X MA Al-Ittihad Tapung Makmur.